Laibach in North Korea — A Journey to the East (from the Slovene Perspective) - Irena Šentevska (Univerzita Karlova, Filozofická fakulta, 2020)
In summer 2015 for the first time in its history the Democratic People’s Republic of Korea welcomed a western rock band, making an unexpected gesture of inviting the Slovene art group Laibach. Laibach’s credentials for this type of cultural diplomacy may be best observed in the sociopolitical context of the 1980s, when they operated within a broader alternative cultural scene of civil society movements in Slovenia (then socialist Yugoslavia). Laibach have since uniquely employed different media and approaches to inspect relations between art, politics, processes of nation-building and popular culture. In the Western media they are mainly presented as a highly controversial music group originating from the former communist East and disturbing the audiences with their totalitarian imagery and ambiguous political messages. Across the globe they were seen as going to North Korea to entertain a brainwashed and utterly unpredictable audience in the most totalitarian and isolated society in the world. This unusual and well documented journey to the far end of what has remained of the former communist East provides interesting material for analyzing the media interpretations of the East/West divide in the contemporary context. However, this paper focuses on the media debate in Slovenia informed by the local knowledge of Laibach’s significance and history which was largely lacking in the international coverage of this out-of-the-ordinary voyage.